Penggunaan Media Pembelajaran Audio Visual Dalam Meningkatkan Semangat Belajar Siswa di Madrasah Aliyah Unggulan Arifah Kabupaten Gowa - Abbas, Nurhamdani; Nadila, Rifka; Sari, Mutiara; Mukramin, Sam'un (CV Putra Publisher, 2023)
This research aims to see how the use of audio-visual learning media increases students' enthusiasm for learning at the Unggulan Arifah Madrasah Aliyah, Gowa Regency, with the research objects being students and teachers. The method used in this research is a qualitative research method, which means that the data collected is in the form of words, images and not numbers. In this research, the data sources used by researchers are primary data sources and secondary data sources. The research instruments used were observation guidelines, interview guidelines and documentation. Data collection techniques include observation, interviews and documentation. The data analysis techniques used in this research are data reduction, data presentation and drawing conclusions and verification. From the research that has been conducted, it can be seen that by using audio-visual learning media, it can be seen that students are very enthusiastic and enthusiastic when learning using audio-visual learning media. This is proven by the students' responses being very active, full of enthusiasm and responding quickly to the teacher in answering questions and daring to put forward answers. They also want video learning media to be presented continuously in learning but also supported by brief explanations by the teacher so that teacher-oriented learning will be slightly reduced.